The health-related quality of life in rheumatoid arthritis, ankylosing spondylitis, and psoriatic arthritis: a comparison with a selected sample of healthy people - Salaffi, Fausto (BioMed Central, 2009)
BACKGROUND: The health-related quality of life (HRQL) is an important indicator of the burden of musculoskeletal disease. The Medical Outcome Study Short-Term 36 (SF-36) is the most used tool that evaluates HRQL as a subjective perception about psychological and physical limitations due to an underlying illness. The purpose of this study was to compare the HRQL scores among patients with rheumatoid arthritis (RA), psoriatic arthritis (PsA) and ankylosing spondylitis (AS) and a selected sample of health people and determine their relationship with measures of clinical condition. METHODS: 799 patients (469 with RA, 164 with AS, 65 with axial PsA and 101 with peripheral PsA) accepted the invitation to participate. 1579 healthy controls were used for the comparison. We calculated scores for the eight SF-36 subscales, the Physical Component Summary (PCS) score, and the Mental Component Summary (MCS) score, according to published algorithms. Disease-related characteristics included disease duration, comorbidity, a measure for disease activity and for radiographic damage. The presence of comorbidity was ascertained through patient's self-reports by the Self-Administered Comorbidity Questionnaire (SCQ). Comparison were performed with respect to sex and age, and s-scores were calculated for comparison with the norm. Multivariate analyses were used to assess the relationship between HRQL and radiographic damage, disease activity, and socio-demographic data. RESULTS: The four inflammatory rheumatic diseases (IRD), compared to controls, significantly impaired all eight health concepts of the SF-36 (p < 0.0001) in both component PCS and MCS scores (p < 0.0001). Overall, the dimensions typically affected were physical functioning, limitations due to physical function, and bodily pain. The disease with the worst HRQL for those dimensions was RA. The multivariate analyses revealed that the physical component was influenced by a high disease activity and comorbidity. The severity of psoriatic lesions was associated with poor mental functioning in patients with PsA. CONCLUSION: Chronic IRD have a clearly detrimental effect on the HRQL in both sex and in age groups, and physical domain is more impaired than mental and social ones.